A pedagogização do frescobol na educação física escolar: uma proposta baseada na pedagogia histórico-crítica - Moraes, Sara Caroliny Marques (2023)
The present work has as object of study the school physical education and the teaching of the sport racquetball in the school. It is justified by the need to look at the manifestation of racquetball body culture as a powerful practice for thematization at school as a content of physical education. However, in the context of hegemony of some school physical education contents, would racquetball be a possible sport/game at school? Is racquetball presented as an overcoming possibility in physical education classes, to reduce the hegemony of certain content? To answer these and other questions, the research, developed during the Professional Master's Degree in Teaching in Basic Education of the Stricto Sensu Graduate Program at CEPAE/UFG, investigated the possibilities for teaching racquetball as a physical education content in a school of the Municipal Education Network of Goiania, intervening with the implementation of a methodological proposal for teaching racquetball, subsidized by the contribution theorist of Critical Historical Pedagogy and Action Research. It was verified that it is possible to diversify the contents of Physical Education through racquetball, even with challenges and limitations, and still present a possibility of racket sport at school, which breaks with the traditionalism of competitive sports. In addition to thematizing racquetball with the 5th grade elementary school students, the intervention aimed at the development of an educational product in the configuration of a didactic sequencer, covering historical, social, cultural, technical, leisure and sports performance aspects, as well as playfulness and cooperativeness belonging to the essence of the game. The educational product “FRESCOBOL AND ITS PEDAGOGICAL PRACTICE AT SCHOOL” is available to those interested in teaching racquetball, especially for physical education teachers, in the appendix and on the EduCapes portal.